The unity of Ibda' and the first intellect: a philosophical criticism of Nasir Kusraw's metaphysic - Ziaee, Ali Akbar (AMIN Research and Cultural Centre, 2011)
The concept of intellect is one of the most important issues in Nasir Khusraw's philosophy. The universal intellect is actual and is the cause of the spiritual and physical worlds and the second is potential and needs an actual intellect to bring it into actuality by imparting to it the knowledge of the realities. I criticized his definition of the first intellect and described his position of ibda (innovation). I deliberated on his relevant philosophical issues and contradictions. I have shown how Nasir Khusraw separated the Divine Command from the First Intellect, while in other places he believe in the unity of them, or in more accurate expression, he considers the First Intellect as an effusion (fayd) of the Divine Command. This apparent contradiction, and more generally the whole question of creation, or manifestation, has always remained among the most debated aspects of many philosophers.